BUAH BIT (Beta vulgaris L.) SEBAGAI ALTERNATIF SAFRANIN PADA PEWARNAAN GRAM - Dian Adhe Bianggo NauE; Karneli Karneli; Anton Syailendra; Indriyani Syafitri; Syafira Wulandari; Widiah Julianti (Husada Mahakam, 2022)
Crystal violet and Safranin are carcinogenic dyes in the Gram stain. Safe alternative materials are needed to minimize the use of carcinogenic properties. Betalain is a pigment of Beetroot (Beta vulgaris L.). The purpose of this study was to determine Beetroot (Beta vulgaris L.) as an alternative of Safranin in bacterial Gram staining. It was an experimental research, where to determine the effectiveness of natural dyes, beetroot was made with concentrations of 75%, 90% and 100% with the addition of HCL. The data in this study using the researcher's observation by looking at the existence of bacterial color in Gram staining with beetroot extract substitute the Safranin. Klebsiella pneumonia was used as the Gram negative bacteria. Neither beetroot juice nor beetroot extract stained the Klebsiella pneumonia. However the Klebsiella pneumoniae stained by 100% concentration of beetroot maceration. It can be concluded that Beetroot is less effective for an alternative of Safranin in bacterial Gram staining.